2012
DOI: 10.5811/westjem.2012.3.11779
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence and Social Pressure among Gay Men in Six Countries

Abstract: IntroductionRecent research suggests that men who have sex with men (MSM) experience intimate partner violence (IPV) at significantly higher rates than heterosexual men. Few studies, however, have investigated implications of heterosexist social pressures – namely, homophobic discrimination, internalized homophobia, and heterosexism – on risk for IPV among MSM, and no previous studies have examined cross-national variations in the relationship between IPV and social pressure. This paper examines reporting of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
5
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(100 citation statements)
references
References 34 publications
2
88
5
5
Order By: Relevance
“…Chard et al (2012), in their transnational research, evidenced the differences in prevalence rates among various countries: participants were recruited through advertisements on Facebook in the United States, Canada, Australia, United Kingdom, Republic of South Africa (RSA), Brazil, Nigeria, Kenya, and India. Their findings showed similar rates between United States and the other nations, while the rate of physical abuse appeared to be similar or more likely to occur in Australia, Brazil, Republic of South Africa, and the United Kingdom than in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Chard et al (2012), in their transnational research, evidenced the differences in prevalence rates among various countries: participants were recruited through advertisements on Facebook in the United States, Canada, Australia, United Kingdom, Republic of South Africa (RSA), Brazil, Nigeria, Kenya, and India. Their findings showed similar rates between United States and the other nations, while the rate of physical abuse appeared to be similar or more likely to occur in Australia, Brazil, Republic of South Africa, and the United Kingdom than in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…One group of studies found that white individuals were significantly less likely to report sexual victimization 3,13,26 . A second group of studies found no significant difference in victimization rates according to skin color 21,30,34,35,36 . A third group (four studies) did not test for statistical significance and found contradictory differences in rates.…”
Section: • Regionmentioning
confidence: 99%
“…Twenty-six studies included women only, four studies men only, and 11 studies both women and men (Table 2). Five studies addressed same-sex sexual aggression 13,14,29,34,35 , and 12 studies provided information on race issues 3,13,21,23,24,26,30,32,34,35,36,37 .…”
Section: • Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of MSSIPV in six countries including the United States, Canada, United Kingdom, Australia, South Africa, and Brazil reported rates of MSSIPV similar to the United States. [19] Generalizability of these results to U.S. populations is limited because of the different cultural structures in these countries.…”
Section: Estimating Mssipvmentioning
confidence: 99%